2022
DOI: 10.1007/s10792-022-02466-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the accuracy of the new-generation intraocular lens power calculation formulae in axial myopic eyes: a meta-analysis

Abstract: Purpose To compare the accuracy of the new-generation intraocular lens power calculation formulae in axial myopic eyes. Methods Four databases, PubMed, Web of Science, EMBASE and Cochrane library, were searched to select relevant studies published between Apr 11, 2011, and Apr 11, 2021. Axial myopic eyes were defined as an axial length more than 24.5 mm. There are 13 formulae to participate in the final comparison (SRK/T, Hoffer Q, Holladay I, Holladay II,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Barrett Universal II was better than T2 ( P = 0.02), and Hill-RBF was better than SRK/T ( P = 0.009). No significant difference was found in other pairwise comparisons [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Barrett Universal II was better than T2 ( P = 0.02), and Hill-RBF was better than SRK/T ( P = 0.009). No significant difference was found in other pairwise comparisons [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Subgroup analysis further demonstrated that the Barrett II outperformed the Haigis for AL ranging from 24.50 to 26.00 mm, but the difference was not statistically significant when the AL exceeded 26.00 mm. Furthermore, an update meta-analysis research by Li et al [ 25 ] suggested that some new-generation, such as Kane, EVO, LSF, Barrett II, and Hill-RBF, showed promising results in IOL power calculation in cataract patients with long AL, with a higher percentage of eyes having predictable outcomes compared to traditional formulas. Previous studies have consistently shown that as the increase of AL, the deviation of IOL power becomes more significant.…”
Section: Discussionmentioning
confidence: 99%
“…In the developmental history of IOL power calculation, an increasing number of formulas have been devised [ 6 - 8 ] to improve precision and accuracy, aiming to avoid the adverse effects caused by miscalculation [ 23 ] . The current study analyzed and mapped the research in the field of IOL power calculation formulas, providing insight into the pace of formula development since the 1940s, and revealing the rapid increase in the last few years.…”
Section: Discussionmentioning
confidence: 99%
“…For trifocal IOLs, the Olsen and Barrett formulas yield the best overall results, with the Kane and Olsen formulas being the most accurate for axial lengths up to 22.5 mm [ 5 ] . New-generation formulas outperform older ones for patients with myopia and short eyes according to two meta-analyses [ 6 , 7 ] . The Barrett Universal II formula is most suitable for normal/long eyes, while the Haigis and EVO formulas are preferred for short eyes according to another study [ 8 ] .…”
Section: Introductionmentioning
confidence: 99%